2020
DOI: 10.7759/cureus.9521
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Outcome of Conduct and Oppositional Defiant Disorder in Children With Attention Deficit Hyperactivity Disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) is one of the most common mental disorders diagnosed in children below the age of 12 years. It is characterized by hyperactivity, inattention, and impulsive behavior. ADHD affects the social, academic, and psychological aspects of children and adolescents. Children with ADHD struggle with school tasks and performance. They have lower grades than their peers and have difficulties interacting with their friends. Oppositional defiant disorder (ODD) is a mental disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Children with ADHD ODD+ may form an intermediate subgroup between ADHD only and ADHD CD+ [ 38 , 39 ]. Some scholars even suggested that ODD is a common feature that is exaggerated in normal adolescents, and it should be considered a temperament dimension rather than a separate categorical disorder [ 3 ]. Therefore, it is not surprising that although the association between ODD and FCs indicated the same association trend as CD, this correlation was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with ADHD ODD+ may form an intermediate subgroup between ADHD only and ADHD CD+ [ 38 , 39 ]. Some scholars even suggested that ODD is a common feature that is exaggerated in normal adolescents, and it should be considered a temperament dimension rather than a separate categorical disorder [ 3 ]. Therefore, it is not surprising that although the association between ODD and FCs indicated the same association trend as CD, this correlation was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…DBD is a common and highly impairing psychiatric disorder characterized by conduct problems, irritability, and oppositional defiant behaviour [ 2 ]. Children with ADHD and DBD (ADHD DBD+ ) have additional impairments and worse prognosis than children with ADHD alone or DBD alone [ 3 , 4 ]. In particular, many empirical studies have shown that comorbid DBD predicts ADHD persistence through adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals experiencing resolution of the disorder in adulthood, while others continue to exhibit symptoms and meet the criteria for antisocial personality disorder (Berluti et al 2023). Childhood-onset conduct disorder has been associated with a poor prognosis, as it increases the risk of developing antisocial personality and substance use disorders in adulthood (Eskander 2020). Furthermore, the prognosis is particularly poor when conduct disorder co-occurs with attention deficit hyperactivity disorder, as this combination is associated with a higher likelihood of antisocial and violent behaviors (Thabrew et al 2017).…”
Section: Prognosismentioning
confidence: 99%
“…Although ADHD and irritability are highly cooccurring and consistently associated with peer functioning impairments, the interplay between these clinical dimensions and peer functioning has rarely been examined. These interactions are particularly relevant given evidence that children who meet the criteria for both ADHD and ODD displayed worse peer relationships (including peer rejection and bullying) than children who meet the criteria for either ADHD or ODD alone (Eskander, 2020;Tseng et al, 2011). Evans et al (2020) examined the longitudinal effects of ADHD and ODD dimensions on peer functioning and found that irritability was concurrently associated with peer rejection and victimization, whereas inattention and hyperactivity-impulsivity robustly predicted subsequent peer rejection and victimization.…”
Section: Introductionmentioning
confidence: 99%
“…Although ADHD and irritability are highly co‐occurring and consistently associated with peer functioning impairments, the interplay between these clinical dimensions and peer functioning has rarely been examined. These interactions are particularly relevant given evidence that children who meet the criteria for both ADHD and ODD displayed worse peer relationships (including peer rejection and bullying) than children who meet the criteria for either ADHD or ODD alone (Eskander, 2020; Tseng et al., 2011). Evans et al.…”
Section: Introductionmentioning
confidence: 99%